INTERAKTIVITAS NARASI DALAM INFOGRAFIS DIGITAL PADA INFOGRAFIS TEMPO.CO - ARI KURNIAWAN; AGUNG EKO BUDIWASPADA; IRFANSYAH IRFANSYAH (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2016)
Online journalism media is now using digital infographic as a new form to narrate the story. They use interactive text and image as a new way to tell a story in the digital space. The digital world has connectivity and depth of information that can be arranged in layers. Understanding digital media as a space that has layers of depth is important because it is distinguish them from the traditional media. This study will discuss one of Tempo.co digital infographics that tells about the corruption of the Constitutional Court’s judge, Akil Mochtar. This digital infographic was analyzed based on the interaction design principles of Donald Norman and interactive narrative models of Heer & Segel. From the analysis, it can be concluded that Interactive element design in this digital infographic has a low level of visibility and inconsistencies in the color-coded feedback, thus reducing the affordance quality of the interactive elements. The interactive element in this digital infographic, wasn’t properly designed based on the understanding of the digital space and the main principles of interaction design. This digital infographics is also not able to maximize the potential of the digital space to make the information flow accompanied by a good narrative. An interactive potential of the digital space should be designed by considering the message that has to be delivered. Interactive elements in digital infographic should be part of the message, not just a mere decoration. Visual, verbal function and interactivity in digital infographic should immerse together, in order to clarify the meaning and narrative of the information. Keywords: infographic; interactivity; naration; online